2010
DOI: 10.1111/j.1574-695x.2010.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage responses to CF pathogens: JNK MAP kinase signaling by Burkholderia cepacia complex lipopolysaccharide

Abstract: Chronic bacterial colonization of the airways with opportunistic pathogens is the primary cause of morbidity and mortality in cystic fibrosis (CF) patients. Burkholderia cepacia complex (Bcc) organisms pose a particular challenge in CF lung disease, due in part to their ability to trigger a fulminant pneumonia. This study compares the U937 macrophage response to two Bcc species, B. cenocepacia and Burkholderia multivorans, against Pseudomonas aeruginosa and Staphylococcus aureus. The two Bcc strains demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…CF macrophages excessively produce the pro-inflammatory cytokine IL-1β in response to B. cenocepacia infection [19], [50]. Human bronchial epithelial cells do not produce IL-1β in response to B. cenocepacia [51].…”
Section: Resultsmentioning
confidence: 99%
“…CF macrophages excessively produce the pro-inflammatory cytokine IL-1β in response to B. cenocepacia infection [19], [50]. Human bronchial epithelial cells do not produce IL-1β in response to B. cenocepacia [51].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown normal IL-1β levels in young CF patients not infected with B. cenocepacia [14,25], elevated levels in adult CF alveolar macrophages not infected with B. cenocepacia [26], and increased IL-1β in non CF macrophages in response to B. cenocepacia [15]. Therefore, it is not clear if IL-1B is specifically increased in CF macrophages upon B. cenocepacia infection.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have shown very little change in IL-1β production over the first years of life [14], whereas others have shown increased IL-1β within subsets of CF patients infected with viruses or various bacterial pathogens [3]. In addition, non CF human macrophages have demonstrated increased IL-1β in response to B. cenocepacia [15], but it is unclear how this response compares to CF macrophages and the overall impact on inflammation in CF. In this study, using the virulent B. cenocepacia J2315 strain, we found increased levels of IL-1β, IL-10, MCP-1, and IFN-γ in infected human CF macrophages, along with increases in cell death and bacterial survival compared to non CF macrophages…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, expression of the cable pilus ( cblA ), as well as a 22 kDa adhesion, are required for the initial adhesion of the bacteria to the surface of lung epithelial cells ( McClean and Callaghan, 2009 ). Moreover, a functional flagella and lipase are necessary for cell invasion ( Tomich et al, 2002 ; Mullen et al, 2007 ), and several other virulence factors enhance the B. cenocepacia pathogenicity, like LPS, metalloprotease, siderophores or secretion systems ( Leitao et al, 2010 ; McKeon et al, 2010 ). Cell-cell communication by quorum sensing (QS), have been described in B. cenocepacia to coordinate expression of these different virulence factors, most of them being necessary for the virulence and also for the normal physiology of B. cenocepacia ( Leitao et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%